Southeast Asia in pre- and post-COVID-19 : economy, society, mobility and religion - Ullah, A. K. M. Ahsan; Chin, Shirley Wei Lee; Noor Hasharina Pengiran Haji Hassan, Dayangku (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"Ullah, Chin and Hassan provide a comprehensive examination of the transformative impact of the COVID -19 pandemic on Southeast Asia, examining its effects on the region's economy, social dynamics, mobility patterns and religious practices. The book examines the profound changes and challenges that the region faced, offering insights into both the immediate responses and the long-term adjustments in these key aspects of Southeast Asian life. An in-depth analysis with a comprehensive and up-to-date perspective on the region's post-pandemic landscape, offering informed insights into the diverse challenges and opportunities facing Southeast Asia in a rapidly changing world. An essential reading for academics, researchers, and policy makers seeking to gain a nuanced understanding of Southeast Asia's response to the pandemic COVID -19"--
Introduction: Uncharted Horizons -- Southeast Asia before and after COVID-19 -- Economy: Southeast Asia in pre- and post-COVID-19 -- Society: What SEA society looked like before and after COVID-19 -- Migration/mobility: Migration pattern in Southeast Asia before and after COVID -- Religion: Traditional practices of religion in SEA before and after COVID-19 -- Conclusion: Pre- and Post-COVID Realities.
Keywords: Southeast Asia -- Economic conditions -- 21st century; Southeast Asia -- Social conditions -- 21st century; Southeast Asia -- Social life and customs -- 21st century; BUSINESS & ECONOMICS / Government & Business; SOCIAL SCIENCE / Emigration & Immigration